Acupuncture transmitted infections. (18th March 2010) - Woo, Patrick C Y; Lin, Ada W C; Lau, Susanna K P; Yuen, Kwok-Yung
Abstract : Are underdiagnosed, so clinicians should have a high index of suspicion